Use of pesticides and intellectual disabilities in local school students. Provincia of Talca, Chile - María T. Muñoz Q (Universidad de Antioquia, 2010)
Objective: to describe the relationship between municipal schools located very close to farms where pesticides are used and the presence of intellectual disabilities in their students. Methodology: this is an exploratory ecological study. Secondary data obtained from school integration programs in the province of Talca were used, and the proximity between schools and farms were also determined. Besides that, rural/urban and socioeconomic level variables were considered. Results: a higher proportion of students with intellectual disabilities from rural schools of low socioeconomic status located very close to farms where pesticides are used was identified with a p < 0.05. Discussion: an investigation related to the association between pesticide exposure and cognitive difficulties among students by means of biomarkers used to determine the effect of pesticides on learning is suggested, thus developing an effective prevention and control of pesticide use.